2020
DOI: 10.1073/pnas.1915387117
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide RNA interference screening reveals a COPI-MAP2K3 pathway required for YAP regulation

Abstract: The transcriptional regulator YAP, which plays important roles in the development, regeneration, and tumorigenesis, is activated when released from inhibition by the Hippo kinase cascade. The regulatory mechanism of YAP in Hippo-low contexts is poorly understood. Here, we performed a genome-wide RNA interference screen to identify genes whose loss of function in a Hippo-null background affects YAP activity. We discovered that the coatomer protein complex I (COPI) is required for YAP nuclear enrichment and that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…We hypothesized that Hippo-independent regulatory mechanisms could serve as viable targets for suppressing YAP activity in cancer. Previously, we performed kinome 5 and whole-genome siRNA screens 27 in LATS1/2-null RPE1 cells to identify regulators of YAP levels that operate independently of Hippo kinases. Because the main effectors of the Hippo signaling cascade, LATS1/2, were inactivated in these cell lines, the cells exhibited significantly increased YAP activity 5 , and we also used these cell lines to screen for Hippo-independent YAP regulation pathways.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that Hippo-independent regulatory mechanisms could serve as viable targets for suppressing YAP activity in cancer. Previously, we performed kinome 5 and whole-genome siRNA screens 27 in LATS1/2-null RPE1 cells to identify regulators of YAP levels that operate independently of Hippo kinases. Because the main effectors of the Hippo signaling cascade, LATS1/2, were inactivated in these cell lines, the cells exhibited significantly increased YAP activity 5 , and we also used these cell lines to screen for Hippo-independent YAP regulation pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous RNAi screening studies suggested that MAP3K3 is a potential target for YAP inhibition 5 , 27 . In this study, we demonstrate that MAP3K3 phosphorylates YAP at serine 405 and that this phosphorylation event interferes with YAP polyubiquitination and lysosomal degradation in a LATS-independent manner.…”
Section: Introductionmentioning
confidence: 99%
“…First, we selected genes that fulfill two conditions as candidates ( SI Appendix , Fig. S2 A and Table S1 ): 1) when depleted, they reduce nuclear YAP protein levels but do not affect the nucleocytoplasmic ratio of YAP, based on our previous siRNA library screening data ( 43 , 44 ); and 2) they are frequently overexpressed and/or amplified in HPV − HNSCC patient samples (TCGA data). We examined the mRNA level of YAP 1 after knockdown of each candidate.…”
Section: Resultsmentioning
confidence: 99%
“…Wong and Thai were also found among the top upregulated ones such as Rap1GAP, CD151, UBE2C and NECTIN2 [30]. MAP2K3 gene (mitogen-activated protein kinase 3) based on the previously published data, has been proposed as a potential drug target due to its activity in lung inflammatory processes (Table 3) [31]. We performed GO (gene ontology) annotation analysis to explore the biological functions of the DEGs in COVID-19 group (Fig.…”
Section: Resultsmentioning
confidence: 99%